Assessing digitalization and data governance issues in Africa - Idris Ademuyiwa; Adedeji Adeniran (Centre for International Governance Innovation (CIGI), 2020)
The growth of digitalization and digital technology adoption in Africa holds the key to strengthening and diversifying economies across the continent. Although these developments offer potentially life-changing benefits for consumers, businesses and governments, the inherent flaws in the digital market mean these benefits are not guaranteed. As most gains from the digital economy are largely concentrated in the United States and China, the digital divide may widen the gap between the Global North and the Global South.
Keywords: 330; Digitalization; Good Governance; E-Business; Africa; Digitalisierung; Good Governance; E-Business; Afrika